Pengaruh Profitabilitas dan Likuiditas serta Leverage terhadap Nilai Perusahaan pada Perusahaan Sektor Retail yang Terdaftar di Bursa Efek Indonesia - Indrawan Prasetya; Wayan Cipta (Universitas Pendidikan Ganesha, 2021)
The purpose of this study was to examine the effect of profitability, liquidity and leverage on firm value. This research was conducted at retail companies listed on the Indonesia Stock Exchange for the 2017-2018 period. The total population is 15 companies. Data were analyzed by multiple linear regression analysis. The results showed that (1) there was a simultaneous influence between profitability, liquidity, and leverage on firm value, with a large contribution of influence of 72.5%, while the remaining 27.5% was influenced by other variables not examined in this study. (2) there is a positive and significant influence between profitability and firm value, (3) there is a positive but insignificant effect between liquidity and firm value, (4) there is a positive and significant influence between leverage and firm value.